Assessment of the analytical guality of the electrolyte analyzer i-Smart 30 PRO for the measur..e ment of serum electrolytes - SANNI, SEKOSSOUNON; Yemoa, Achille; BIGOT, CEDRIC PARFAIT; KPOSSOU, PAUL; Faihun Joachim, Liliane; BIGOT, KOFFI ANDRÉ (My University, 2018)
The i-Smart 30 PRO electrolyte analyzer is an electrochemical analyzer used to measure the concentrations 0 sodium, potassium and chlorides in various biological flùids. The airn of this study was to assess the analytical quality of the electrolyte analyzer i-Smart 30 PRO and validate its use for electrolytes testings at the Laboratory of Clinical Biochemistry and Toxicology, National Teaching Hospital Hubert Koutoukou MAGA. Samples received routinely for sodium, potassium and chlorides testings were runned on the electrolyte ana1yzers i-Smart 30 PRO and ILyte used as the gold standard. The sodium, potassium and chlorides serum concentrations were biased with significant differences. However more than 95% of the testings results were within the 95% limits of agreement. The i-Smart 30 PRO electrolyte analyzer could validly replace the ILyte analyzer for the measurements of these electrolytes concentrations in serum.
Keywords: Electrolytes; testings; analyzer; validation; i-Smart 30 PRO; ILyte.